Robot-assisted versus conventional laparoscopic surgery for endometrial cancer: long-term comparison of outcomes - Eoh, Kyung Jin; Kim, Tae-Joong; Park, Jeong-Yeol; Kim, Hee Seung; Paek, Jiheum; Kim, Young Tae (Frontiers in Oncology, 2023)
Objective: There is a lack of multi-institutional large-volume and long-term follow-up data on comparisons between robot-assisted surgery and conventional laparoscopic surgery. This study compared the surgical and long-term survival outcomes between patients who underwent robot-assisted or conventional laparoscopic surgery for endometrial cancer. Methods: We retrospectively reviewed the data of patients from five large academic institutions who underwent either robot-assisted or conventional laparoscopic surgery for the treatment of endometrial cancer between 2012 and 2017, ensuring at least 5 years of potential follow-up. Intra- and postoperative outcomes, long-term disease-free survival, and overall survival were compared. Results: The study cohort included 1,003 unselected patients: 551 and 452 patients received conventional laparoscopic and robot-assisted surgery, respectively. The median follow-up duration was 57 months. Postoperative complications were significantly less likely to occur in the robot-assisted surgery group compared to the laparoscopic surgery group (7.74% vs. 13.79%, P = 0.002), primarily limited to minor complications. There were no significant differences in survival: 5-year disease-free survival was 91.2% versus 90.0% (P = 0.628) and overall survival was 97.9% versus 96.8% (P = 0.285) in the robot-assisted and laparoscopic surgery cohorts, respectively. Cox proportional hazard regression models demonstrated that the mode of surgery was not associated with disease-free survival (hazard ratio, 0.897; confidence interval, 0.563–1.429) or overall survival (hazard ratio, 0.791; confidence interval, 0.330–1.895) after adjusting for confounding factors. Conclusions: Robot-assisted surgery for endometrial cancer demonstrates comparable long-term survival outcomes and a reduced incidence of postoperative minor complications when compared to conventional laparoscopic surgery.